Role of autophagy in cancer-associated fibroblast activation, signaling and metabolic reprograming - Sari, Dyana; Gozuacik, Devrim; Akkoc, Yunus (Frontiers in Cell and Developmental Biology, 2024)
Tumors not only consist of cancerous cells, but they also harbor several normal-like cell types and non-cellular components. Carcinoma-associated fibroblasts (CAFs) are one of these cellular components that are found predominantly in the tumor stroma. Autophagy is an intracellular degradation and quality control mechanism, and recent studies provided evidence that autophagy played a critical role in CAF formation, metabolic reprograming and tumor-stroma crosstalk.Therefore, shedding light on the autophagy and its role in CAF biology might help us better understand the roles of CAFs and the TME in cancer progression and may facilitate the exploitation of more efficient cancer diagnosis and treatment. Here, we provide an overview about the involvement of autophagy in CAF-related pathways, including transdifferentiation and activation of CAFs, and further discuss the implications of targeting tumor stroma as a treatment option.